Laser Illumination Adjustments for Signal-to-Noise Ratio and Spatial Resolution Enhancement in Static 2D Chemical Images of NbOx/IGZO/ITO/Glass Light-Addressable Potentiometric Sensors - Chun-Hui Chen (MDPI AG, 2021)
In a previous study, a thin In-Ga-Zn-oxide light addressable potentiometric sensor (IGZO LAPS) was indicated to have the advantages of low interference from ambient light, a high photocurrent and transfer efficiency, and a low cost. However, illumination optimization to obtain two-dimensional (2D) chemical images with better spatial resolutions has not been fully investigated. The trigger current and AC-modulated frequency of a 405-nm laser used to illuminate the fabricated IGZO LAPS were modified to check the photocurrent of the sensing area and SU8–2005 masking area, obtaining spatial resolution-related functions for the first time. The trigger current of illumination was adjusted from 0.020 to 0.030 A to compromise between an acceptable photocurrent and the integrity of the SU8–2005 masking layer. The photocurrent (PC) and differential photocurrent (DPC) versus scanning length (SL) controlled by an X-Y stage were used to check the resolved critical dimensions (CDs). The difference between resolved CD and optically measured CD (e.g., delta CD) measured at an AC frequency of 500 Hz revealed overall smaller values, supporting precise measurement in 2D imaging. The signal-to-noise ratio (SNR) has an optimized range of 2.0 to 2.15 for a better resolution for step spacings of both 10 and 2 μm in the scanning procedure to construct static 2D images. Under illumination conditions with a trigger current of 0.025 A and at an AC frequency of 500 Hz, the spatial resolution can be reduced to 10 μm from the pattern width of 6 μm. This developed methodology provides a quantitative evaluation with further optimization in spatial resolution without an extra cost for applications requiring a high spatial resolution, such as single-cell activity.